Point-of-care testing of nitrite in oral medicine - Application and validation of an enzymatic biosensor in human saliva - Sara Rodrigues Gaspar; Luís Proença; Ricardo Alves; Maria Gabriela Almeida (Sensing and Bio-Sensing Research)
Periodontal disease (PD) is a chronic inflammatory condition triggered by bacterial biofilms and progresses through two main stages: gingivitis and periodontitis. The existing diagnostic methods remain time-consuming and require clinical expertise. Salivary nitrite, a stable end-product of nitric oxide produced during inflammation, has emerged as a promising biomarker for PD. However, its reliable quantification in saliva typically relies on laboratory-based assays that are unsuited to clinical workflows.This study aimed to test and validate a new nitrite point-of-care test (POCT) for oral medicine. Building on previous research, we developed a biosensing platform based on screen-printed carbon electrodes modified with a selective enzyme, the cytochrome c nitrite reductase. To adapt bioelectrodes for salivary analysis, they were further modified with a poly(vinyl) alcohol coating and a biochemical oxygen scavenger system (ascorbate oxidase and ascorbate). The nitrite biosensor achieved a suitable linear range of 5–300 μM, with a sensitivity of 0.015 μM−1, validated against the gold-standard Griess method. Unlike the Griess reaction, the biosensor was unaffected by sample turbidity, rendering centrifugation unnecessary. Additionally, we observed that sample freezing altered nitrite concentrations, increasing levels in non-centrifuged samples, while decreasing them in previously clarified samples. These findings highlight the need for real-time analysis and call into question the reliability of previously published data that overlooked these variables. Therefore, our results demonstrate the potential of the nitrite biosensor as a novel salivary POCT and emphasize the critical need for standardized sample-handling protocols.